Occurrence of Bimodal Classroom Achievement in Ontario - Sibbald, Timothy (Alberta Journal of Educational Research, 2014)
The occurrence of bimodality in classroom distributions of student achievement is assessed for a population sample of 143,925 Ontario grade 9 students in 6,943 classrooms using standardized assessment scores. A pattern recognition approach―which makes no assumptions about the underlying latent variables―was used to identify the number of modes. The resulting finding was that one quarter of classrooms exhibit bimodal characteristics, with approximately 20% having two modes and 5% having three modes.